Orientasi sikap keusahawanan di kalangan pelajar Sekolah Menengah Lambor Kiri Perak - Hisan Mohd Sudin (Tanjong Malim, 2007)
Orientasi sikap keusahawanan di kalangan pelajar Sekolah Menengah Lambor Kiri Perak by Hisan Mohd Sudin